Pengelolaan Destinasi Wisata Era New Normal dalam Pemberdayaan Masyarakat Lokal di Desa Kesiman Kertalangu Kota Denpasar - I Gusti Ayu Intan Chandra Dewi; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Warmadewa Press, 2022)
The outbreak of the COVID-19 pandemic has devastated the Bali tourism industry. In response to this, the Government issued a New Normal Era Tourism policy, especially in reconstructing the empowerment of local tourism. This study discusses the management of new normal era tourist destinations in empowering local communities in Kesiman Kertalangu Village, Denpasar City. The purposes of this study are to reveal the governance model of new normal era tourist destinations in Kesiman Kertalangu Village, Denpasar City and the role of the Kesiman Kertalangu Village Government in empowering local communities in managing new normal era tourist destinations. The research method applied is empirical research with a sociological approach. The data collection technique was carried out using observation techniques through interviews with informants and respondents. The sources of legal materials used are primary and secondary legal sources. The legal material analysis technique used is descriptive analysis technique. The results of this study reveal that the new normal era tourism destination management model in Kesiman Kertalangu Village is carried out in collaboration between the Village Government and BUMDes and investors by implementing health protocol management according to procedures. The role of the Kesiman Kertalangu Village Government in empowering local communities in the management of tourist destinations is proven by involving BUMDes and forming Village Regulations and Perbekel Regulations as legal protection for the management of tourist destinations that prioritize the empowerment of local communities, especially in the new normal era.